Hidden participation in the public sphere: understanding Malaysian university students' public discourse practices in cyberspace - Chan, Mei Yuit; Rafik-Galea, Shameem; Yap, Ngee Thai (2014)
A recent development in Malaysia was the unprecedented rise in young Malaysians’ participation in the country’s social and political affairs, facilitated almost entirely by the Internet. This phenomenon caught many by surprise considering that university students in the country had been barred through legislation from active involvement in political activities for more than 30 years. Through a survey of 514 university students in a Malaysian public university, supplemented by interview data and samples of students’ writing, this study investigated in which ways Malaysian tertiary students are participating in the public sphere through the Internet. Following Hauser’s (1999) conception of public discourse as personal, interactive, informal, and distributed voices among the citizenry, we argue for a perspective that explains how online interactions in the friendship frame among young people represent their participation in the public sphere in the context of contemporary society.